Implications of event attribution for loss and damage policy. (3rd September 2015) - Parker, Hannah R.; Cornforth, Rosalind J.; Boyd, Emily; James, Rachel; Otto, Friederike E. L.; Allen, Myles R.
<x xml:space="preserve">Abstract</x> The United Nations Framework Convention on Climate Change (UNFCCC) has established the Warsaw International Mechanism (WIM) to deal with loss and damage associated with climate change impacts, including extreme events, in developing countries. It is not yet known whether events will need to be attributed to anthropogenic climate change to be considered under the WIM. Attribution is possible for some extreme events ‐ a climate model assessment can estimate how greenhouse gas emissions have affected the likelihood of their occurrence. Dialogue between scientists and stakeholders is required to establish whether, and how, this science could play a role in the WIM.